2002
DOI: 10.1021/ja012499i
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Light-Driven Molecular Motors. Unidirectional Rotation Controlled by a Single Stereogenic Center with Near-Perfect Photoequilibria and Acceleration of the Speed of Rotation by Structural Modification

Abstract: Nine new molecular motors, consisting of a 2,3-dihydro-2-methylnaphtho[2,1-b]thiopyran or 2,3-dihydro-3-methylphenanthrene upper part and a (thio)xanthene, 10,10-dimethylanthracene, or dibenzocycloheptene lower part, connected by a central double bond, were synthesized. A single stereogenic center, bearing a methyl substituent, is present in each of the motors. MOPAC93-AM1 calculations, NMR studies, and X-ray analysis revealed that these compounds have stable isomers with pseudoaxial orientation of the methyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
391
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(412 citation statements)
references
References 51 publications
(50 reference statements)
10
391
1
5
Order By: Relevance
“…24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors. From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors. From such studies, it has been found that one way of lowering the thermal freeenergy barriers of type IIa motors is to contract the sizes of the rotator and stator by employing a cyclopenta[a]naphthalenylidene rotator and a fluorene stator, as done in type IIb motors.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Several examples of such systems known as either first-generation or second-generation rotary molecular motors are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more pronounced effect is seen when X is altered. By changing from X = S (6) to X = CH 2 (8), the half-life for the thermal isomerization step could be decreased from 215 h to 40 min at room temperature [29]. Much to our surprise, in the motor systems 9 and 10, shown in Fig.…”
Section: Methodsmentioning
confidence: 81%
“…Due to the dynamic controllability of unidirectional rotation, the stereoselectively chiroptical inversion between the stable ( P ) form and the unstable ( M ) form is reversible with a variable half‐life by structural modification from 8 ns to 1.4 × 10 3 years 47, 48, 49, 50. The resulting tunability of geometrical charity has been significantly investigated to create photoactiving chiral catalysts in solvents51, 52 and polar switchovers on solid surfaces 53, 54, 55.…”
Section: Introductionmentioning
confidence: 99%